2016
DOI: 10.1108/jpif-12-2014-0070
|View full text |Cite
|
Sign up to set email alerts
|

Integration between the Asian REIT markets and macroeconomic variables

Abstract: Purpose – The purpose of this paper is to examine the long-run relationship and short-term linkage between the Asian REIT markets and their respective macroeconomic variables. Design/methodology/approach – The data collected comprised total return REIT Index from Japan, Hong Kong, Singapore, Malaysia, Thailand, Taiwan and South Korea and their macroeconomic variables from the date of availability of the data until December 2014. The macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…3 shows a co-integration between REIT return and MMI suggesting that previous time series data (values) of the MMIs can predict significantly the REIT dividend return in both short term and long term. This finding agrees with Swanson et al (2002, Chui et al (2003and Mai'n et al (2016 Loo et al (2016) and Olanrele et al (2017). The finding of REIT return being significantly related to TBR corroborates similar relationship to bond coupon rate reported by Nittayagosetwat and Buranasiri (2012) and Astrious and Bogiazi (2013).…”
Section: _______________________________________________________ 319supporting
confidence: 91%
See 1 more Smart Citation
“…3 shows a co-integration between REIT return and MMI suggesting that previous time series data (values) of the MMIs can predict significantly the REIT dividend return in both short term and long term. This finding agrees with Swanson et al (2002, Chui et al (2003and Mai'n et al (2016 Loo et al (2016) and Olanrele et al (2017). The finding of REIT return being significantly related to TBR corroborates similar relationship to bond coupon rate reported by Nittayagosetwat and Buranasiri (2012) and Astrious and Bogiazi (2013).…”
Section: _______________________________________________________ 319supporting
confidence: 91%
“…REITs returns and general stock market Loo, Annuar and Ramakrishan (2016). concluded that emerging REITs markets are more sensitive to macroeconomic variables changes than the established REITs markets i.e.…”
mentioning
confidence: 99%
“…The Johansen co-integration test result by both Trace and Max-Eigen values in Table 3 shows a co-integration between REIT return and MMI suggesting that previous time series data (values) of the MMIs can predict significantly the REIT dividend return in both short term and long term. This finding agrees with Swanson et al (2002, Chui et al (2003and Mai'n et al (2016 reported by Islam (2003), Loo et al (2016) and Olanrele et al (2017). The finding of REIT return being significantly related to TBR corroborates similar relationship to bond coupon rate reported by Nittayagosetwat and Buranasiri (2012) and Astrious and Bogiazi (2013).…”
Section: _______________________________________________________ 319supporting
confidence: 90%
“…In fact, developed markets are more stable and thus macroeconomic indicators, such as unemployment rate, inflation, interest rates tend to be less volatile. Several studies highlighted that the REITs of emerging markets are more sensitive to macroeconomic variables compared to the REITs of developed markets due to large spreads and high volatility in inflation, unemployment and interest rates; therefore, that emerging markets are fundamentally different to developed markets (Loo et al, 2016;Akinsomi et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%